Peritoneal Equilibration Test Reference Values Using A 3.86% Glucose Solution during the First Year of Peritoneal Dialysis: Results of a Multicenter Study of a Large Patient Population. Issue 6 (November 2017) - Milia, Vincenzo La; Cabiddu, Gianfranca; Virga, Giovambattista; Vizzardi, Valerio; Giuliani, Anna; Finato, Viviana; Feriani, Mariano; Filippini, Armando; Neri, Loris; Lisi, Lucia
Background: The original peritoneal equilibration test (PET) was used to classify peritoneal dialysis (PD) patients using a 2.27% glucose solution. It has since been suggested that a 3.86% glucose solution be used because this provides better information about ultrafiltration (UF) capacity and the sodium (Na) sieving of the peritoneal membrane. Objective: The aim of this study was to determine reference values for a PET using a 3.86% glucose solution (PET-3.86%). Methods: We evaluated the PET-3.86% in a large population of incident PD patients attending 27 Italian dialysis centers. Results: We evaluated the results of 758 PET-3.86% in 758 incident PD patients (1 test per patient). The mean duration of PD was 5 ± 3 months. The ratio of the concentrations of creatinine in dialysate/plasma (D/PCreat ) was 0.73 ± 0.1 (median 0.74). The ratio between the concentrations of glucose at the end/beginning of the test (D/D0 ) was 0.25 ± 0.08 (median 0.24). Ultrafiltration uncorrected and corrected for bag overfill was respectively 776 ± 295 mL (median 781 mL) and 675 ± 308 mL (median 689 mL). Sodium sieving was 8.4 ± 3.8 mmol/L (median 8.0 mmol/L). Conclusion: The results of the study provide PET-3.86% reference values for the beginning of PD that can be used to classify PD patients into transport classes and monitor them over time.